Application of Pancasila as the Ethical System of the Indonesian Nation - Susilawati N; Bambang Niko Pasla (Jurnal Prajaiswara, 2020)
Ethics is related to good living habits, and good living procedures, for individuals or society. In this sense, ethics is the same as morals. Ethics in a broad sense is the science that discusses the criteria of good and bad. Ethics are generally understood as philosophical thoughts about everything that is considered good or bad in human behavior. Ethics is always related to the issue of values ​​so the discussion about ethics generally talks about issues of good or bad values. Pancasila as an ethical system is very urgent to be applied in the life of a nation and state because of the problems faced by the Indonesian people, among others: 1) The many cases of corruption that hit the State of Indonesia so as to weaken the joints of life as a nation and state, 2) The occurrence of acts of terrorism in the name of religion so that it can damage the spirit of tolerance in inter-religious life, and melt the spirit of unity or threaten the disintegration of the nation, 3) Human rights violations still occur in the life of the state, 4). The gap between rich and poor groups still marks the lives of Indonesian people, 5) legal injustice that still colors the judicial process in Indonesia and 6) Many rich people are not willing to pay taxes properly. The strategy for implementing Pancasila as an ethical system in the life of the nation and state for the Indonesian people is carried out as follows: 1) Character education. 2) Reference Criteria for State Administrators, 3) Raising Awareness of Taxpayers, 4) Manifestation of the Pancasila Value in the Human Rights Law and 5) Manifestation of the Pancasila Value in the Environmental Law.